2017
DOI: 10.1149/07801.1615ecst
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Observation of Co-Ce Coated Metallic Interconnect Oxidation Combined with High-Resolution Post Exposure Analysis

Abstract: Oxidation of Sanergy SSHT steel with Ce-Co coating, used as interconnect material, was observed in-situ in a modified environmental scanning electron microscope (ESEM) at nominal temperature between 800°C and 900°C under 33Pa of oxygen, for different durations (up to 60h). After these in-situ observations, lamellas of the observed target areas were prepared using a focused ion beam (FIB). This allowed the evaluation in the cross section of the final composition of the oxidation layers of the steel by scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…After 3000 h of oxidation, the Cr 2 O 3 layer thickened and the inner Cr 2 MnO 4 spinel layer was dissolved, while the surface layer of (Co, Fe, Mn) 3 O 4 remained stable. Poitel et al [33] confirmed the diffusion behavior of Fe and Mn from the metal substrate to the Co coating at high temperature via an in situ observation with a modified environmental scanning electron microscope (ESEM). Karlsson et al [34,35] characterized the microstructure variations of 800 nm-thick Ce-Co/Mn coatings with time using scanning transmission electron microscopy (STEM) and electron energy loss spectroscopy (EELS).…”
Section: Discussionmentioning
confidence: 95%
“…After 3000 h of oxidation, the Cr 2 O 3 layer thickened and the inner Cr 2 MnO 4 spinel layer was dissolved, while the surface layer of (Co, Fe, Mn) 3 O 4 remained stable. Poitel et al [33] confirmed the diffusion behavior of Fe and Mn from the metal substrate to the Co coating at high temperature via an in situ observation with a modified environmental scanning electron microscope (ESEM). Karlsson et al [34,35] characterized the microstructure variations of 800 nm-thick Ce-Co/Mn coatings with time using scanning transmission electron microscopy (STEM) and electron energy loss spectroscopy (EELS).…”
Section: Discussionmentioning
confidence: 95%
“… and Poitel et al. show that the oxidation of the metallic Co layer is a fast process compared to the measurement times. Froitzheim have demonstrated that oxidation of a similar 640 nm metallic Co layer in 850 °C takes place in less than 30 s.…”
Section: Methodsmentioning
confidence: 92%
“…The Co coating reacts with manganese diffusing from the bulk steel and forms a (Mn,Co) 3 O 4 spinel, whereas the cerium layer further aids to hinder chromia formation [31]. Studies by Froitzheim et al [32] and Poitel et al [33] show that the oxidation of the metallic Co layer is a fast process compared to the measurement times. Froitzheim have demonstrated that oxidation of a similar 640 nm metallic Co layer in 850°C takes place in less than 30 s.…”
Section: Test Setupmentioning
confidence: 99%
“…In recent years, the use of HT-ESEM has become increasingly popular due to its ability to provide in-situ imaging and analysis in controlled atmospheres and elevated temperatures [9]. While HT-ESEM has been used to investigate topics such as the morphology and structural transformation of Al-Si coated boron steel [10] and the oxidation of Co-Ce coated interconnect steel [11], and recently, observing the bainite formation in a medium carbon steel [12], it has yet to be extensively utilized in NMI research within the steel industry. During hot rolling of steel, the phase composition of NMIs determines their tendency for elongation and fragmentation [13].…”
Section: Introductionmentioning
confidence: 99%